Virological Profiles in Patients With Chronic Hepatitis C and Overt Or Occult Hbv Infection - Squadrito, Giovanni; Orlando, Maria Elena; Pollicino, Teresa; Raffa, Giuseppina; Restuccia, Tea; Cacciola, Irene; Di Marco, Vito; Picciotto, Antonio; Colucci, Giuseppe; Craxì, Antonio; Raimondo, Giovanni (The American journal of gastroenterology, 2002)
The virological profiles of hepatitis B and C viruses (HBV and HCV) and their interplay in cases of coinfection are undefined. A suppressed and occult HBV infection may occur in hepatitis B surface antigen (HBsAg) negative patients with chronic hepatitis C. The HCV core protein is able to inhibit HBV “in vitro,” and serines at positions 99 and 116 are essential for such inhibition. We aimed to assess the HBV and HCV virological profiles in cases of coinfection and to evaluate the relationship between HCV core gene variability and HBV activity. Eighty-two anti-HCV positive patients were examined35 cases were HBsAg positive, 24 were HBsAg negative with “occult” HBV infection, and 23 were HBV negative. HBV and HCV viremia levels were evaluated in all cases. HCV genomic region coding for the aminoacid sequence 99–116 of core protein was amplified and sequenced in all HCV RNA positive cases. The entire core gene was amplified and sequenced in three randomly selected cases. Serum HCV RNA was detected in all cases but 13, all HBsAg positive individuals; HCV viremia levels of the other 22 HBsAg positive subjects were similar to those detected in HBsAg negative patients with or without occult HBV infection. Among the 35 HBsAg positive patients both HBV DNA and HCV RNA were detected in five cases, HCV RNA alone in 17, and HBV DNA alone in six, whereas seven cases had undetectable levels of both viruses. Sequencing analyses showed that the HCV core gene was highly preserved in all patients. A wide spectrum of HCV and HBV virological patterns may occur in a case of coinfection. HCV core variability is not related to HBV activity “in vivo.”